Anxiety and its coping mechanisms among engineering and medical students: a comparative study - Maryam Tariq,; Muhammad Arham,; Suqrat, Humayun; Qaisar Sohail, (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the frequency of anxiety and its coping mechanism among medical and engineering students. Method: The comparative cross-sectional study was conducted from April to September 2023 in Faisalabad, Pakistan, and comprised students from two medical and two engineering education institutions. Within the two subsets, one was a public-sector institution and the other was in the private sector. Data was collected using Generalised Anxiety Disorder-7 and Brief Cope Inventory. Data was Analysed using SPSS 27. Results: Study subjects ranged between 17-26 years of age and 144(36%) of them were females. Of the 400 subjects, 200(50%) were medical students and the rest were engineering students uniformly representing all years of education. Also, 200(50%) responses were from private-sector institutions and the rest were from public-sector institutions. Mild anxiety was present in 220(55%) subjects, more in engineering students. Moderate anxiety was found in 98(24.5%) students, most in public-sector medical institutions. Minimal and severe anxiety were noted in 56(14%) and 26(6.50%) subjects, respectively. Medical and engineering students showed the same patterns of coping mechanisms, with planning (2.55±0.69) being the most adopted, and substance abuse (1.78±0.68) the least. Conclusion: Except for mild anxiety, all other groups of anxiety levels were found to be higher among medical students. In terms of coping behaviour, there was no difference between medical and engineering students. Key Words: Anxiety, Coping mechanism, Coping strategy.